The saddest pony - Betancourt, Jeanne; Illustrated by Kubbos, Vivien (Sydney Scholastic, 1998)
"Pam and Lightning discover an old pony, in a farmhouse shed, that appears neglected. Lulu and Anna, Pam's Pony Pals, agree. This is the saddest pony they have ever seen. Who owns the pony? And why aren't they caring for her properly? First, the Pony Pals must find out who owns the pony. Will they be able to help the sad pony?"--Back cover.
Include Illustration
Keywords: Ponies -- Horses